Higher Order Approximation to Achieve Almost Constant Modulated SRS Power including Pulse Walk off Effect and Data Transmission Formats - Kumari, Kamini (My University, 2015)
The nonlinear effects degrade the performance of system. When optical power is very high nonlinear effect occurs, there study became important in DWDM system. The two types of nonlinearities occur in optical fibers are:-  Stimulated scattering such as SRS and SBS  Optical Kerr effect, due to changes in the refractive index of fiber with optical power. Depending upon the type of input sign Kerr-non-linearity represented in three different types of effects such as Self-Phase Modulation (SPM), Cross-Phase Modulation (CPM) and Four-Wave Mixing (FWM). At high power level, the inelastic scattering phenomenon can induce Stimulated effects such as Stimulated Brillouin-Scattering (SBS) and Stimulated Raman-Scattering (SRS). if the incident power exceeds a certain threshold value the intensity vary linearly. Difference between SRS and SBS are:- 1. SRS generated optical phonon are incoherent while SBS generated acoustic phonon are coherent. 2. SRS threshold is close to 1 w which is 100 times higher than SBS threshold. 3. Scattered light shifted in frequency is 13 THz in SRS while in SBS is 10 GHz. Hence frequency shift is maximum in SRS. 4. SRS is much less problem than SBS. 5. SRS bandwidth is 572 mW and in SBS bandwidth is narrow i.e. 1.289 mW. In this Dissertation stimulated Raman scattering model has been study and presented a higher order approximation to achieve almost constant modulated SRS power including pulse walk off effect and data formats. The data format such as RZ, NRZ and optical Manchester discussed in briefly. Constant modulated power is produce using pulse walk off. Due to SRS effect, channel at shorter wavelength act as pump for the longer channel act as iv stokes. To reduce SRS effect or to achieve almost constant modulated power pulse walk off rule is applied. Power tilt Because of SRS effect has been calculated at RZ, NRZ and optical Manchester format. Power has been varied from 1 to 60 mW. Using pulse walk off rule effect on channel was done. Pulse walk off rule limit the effective length and number of channels increases. Using this algorithm, efficiency is also increased.
M.E. (ECED)
Keywords: SRS; SBS; ECED